Post-hoc Analysis of Outcome of Intravenous Thrombolysis in Infarcts of Infratentorial Localization in the WAKE-UP Trial - Galinovic, Ivana; Boutitie, Florent; Fiebach, Jochen B.; Villringer, Kersten; Cheng, Bastian; Ebinger, Martin; Endres, Matthias; Fiehler, Jens; Ford, Ian; Thijs, Vincent; Lemmens, Robin; Muir, Keith W.; et al. (Frontiers in Neurology, 2019)
Introduction In WAKE-UP (Efficacy and Safety of MRI-based Thrombolysis in Wake-Up Stroke), patients with an acute stroke of unknown onset time were randomized to treatment with intravenous alteplase or placebo, guided by MRI. Methods In this exploratory post-hoc secondary analysis we compared clinical and imaging data, as well as treatment effects and safety of intravenous thrombolysis between patients with infra- vs supratentorial stroke. Results Forty-eight out of 503 randomized patients (9.5%) presented with a stroke involving the cerebellum or brainstem. Patients with infratentorial stroke were younger compared to patients with supratentorial stroke (mean age 60 vs 66 years), more frequently male (85% vs 62%), and less severely affected (median NIHSS 4.5 vs 6.0). There was no heterogeneity for treatment effect between supratentorial (OR 1.67 95% CI 1.11 – 2.51) and infratentorial (OR 1.31 95% CI 0.41 – 4.22) sub-groups (test for interaction p=0.70). In patients with infratentorial stroke, favorable outcome (a score of 0-1 on the modified Rankin scale (mRS) at 90 days) was observed in 12/22 patients (54.5%) in the alteplase group and in 13/25 patients (52.0%) in the placebo group (p=0.59). The primary safety endpoint (death or mRS 4-6 at day 90) occurred in 3 patients of the alteplase group (13.6%) and 3 patients in the placebo group (12.0%); p=0.74. Discussion WAKE-UP was underpowered for demonstrating treatment effect in subgroup analyses however, based on our current results, there is no evidence to recommend withholding MRI-guided thrombolysis in patients with unknown onset stroke of infratentorial localization.